AL amyloid imaging and therapy with a monoclonal antibody to a cryptic epitope on amyloid fibrils. - Jonathan S Wall; Stephen J Kennel; Angela Williams; Tina Richey; Alan Stuckey; Ying Huang; Sallie Macy; Robert Donnell; Robin Barbour; Peter Seubert; Dale Schenk (PLoS ONE, 2012)
The monoclonal antibody 2A4 binds an epitope derived from a cleavage site of serum amyloid protein A (sAA) containing a -Glu-Asp- amino acid pairing. In addition to its reactivity with sAA amyloid deposits, the antibody was also found to bind amyloid fibrils composed of immunoglobulin light chains. The antibody binds to synthetic fibrils and human light chain (AL) amyloid extracts with high affinity even in the presence of soluble light chain proteins. Immunohistochemistry with biotinylated 2A4 demonstrated positive reaction with ALκ and ALλ human amyloid deposits in various organs. Surface plasmon resonance analyses using synthetic AL fibrils as a substrate revealed that 2A4 bound with a K(D) of ∼10 nM. Binding was inhibited in the presence of the -Glu-Asp- containing immunogen peptide. Radiolabeled 2A4 specifically localized with human AL amyloid extracts implanted in mice (amyloidomas) as evidenced by single photon emission (SPECT) imaging. Furthermore, co-localization of the radiolabeled mAb with amyloid was shown in biodistribution and micro-autoradiography studies. Treatment with 2A4 expedited regression of ALκ amyloidomas in mice, likely mediated by the action of macrophages and neutrophils, relative to animals that received a control antibody. These data indicate that the 2A4 mAb might be of interest for potential imaging and immunotherapy in patients with AL amyloidosis.